Design of State Evaluation Platform for Distribution Automation Terminal unit Based on AHP. Issue 6 (March 2020) - Xiao, Jinxing; Yao, Kaiqiang; Huang, Liangliang; Tang, Heng
Abstract: The requirement of modern power grid for distribution automation is becoming more and more stringent and standardized. Aiming at the situation that the large number of distribution automation terminal units brings to for a lot of inconvenience of maintenance work, this paper establishes a state evaluation system of distribution automation terminal unit based on AHP, and designs a software platform for the system. The software platform occupies little memory, and has friendly interface and is simple. It only needs to input the state of the terminal unit to get the evaluation level of the terminal unit. The software platform can also modify the weight score of each index according to the evaluation results, to constantly revise the judgment matrix and evaluate the terminal more accurately. It provides a reference for terminal state control of distribution automation.